Comparing transcriptional activation and autostimulation by ZEBRA and ZEBRA/c-Fos chimeras. - Kolman, J L (1996)
The lytic cycle of Epstein-Barr virus (EBV) can be activated by transfection of the gene for ZEBRA, a viral basic-zipper (bZip) transcriptional activator. ZEBRA and cellular AP-1 bZip activators, such as c-Fos, have homologous DNA-binding domains, and their DNA-binding specificities overlap. Moreover, EBV latency can also be disrupted by phorbol esters, which act, in part, through AP-1 activators. It is not known whether ZEBRA and AP-1 factors play equivalent roles in the initial stages of reactivation. Here the contribution of ZEBRA's basic DNA recognition domain to disruption of latency was analyzed by comparing ZEBRA with chimeric mutants in which the DNA recognition domain of ZEBRA was replaced with the analogous domain of c-Fos. Chimeric ZEBRA/c-Fos proteins overexpressed in Escherichia coli bound DNA with the specificity of c-Fos; they bound a heptamer AP-1 site and an octamer TPA response element (TRE). ZEBRA bound the AP-1 site and an array of ZEBRA response elements (ZREs). In assays with reporter genes, both ZEBRA and ZEBRA/c-Fos chimeric mutants activated transcription from Zp, a promoter of the ZEBRA gene (BZLF1) that contains the TRE and multiple ZREs. However, despite their capacity to activate reporters bearing Zp, neither ZEBRA nor the c-Fos chimeras activated transcription from Zp in the context of the intact latent viral genome. In contrast, ZEBRA but not ZEBRA/c-Fos chimeras activated Rp, a second viral promoter that controls ZEBRA expression. Hence, transcriptional autostimulation by transfected ZEBRA occurred preferentially at Rp. Both ZEBRA and the ZEBRA/c-Fos chimeras activated transcription from reporters with multimerized AP-1 sites. However, in the context of the virus, only ZEBRA activated the promoters of two early lytic cycle genes, BMRF1 and BMLF1, that contain an AP-1 site. Thus, overexpression of an activator that recognized AP-1 and TRE sites was not sufficient to activate EBV early lytic cycle genes.